2022
DOI: 10.3390/molecules27196163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Extraction Methods on the Phenolic Profile and the Antioxidant Potential of Ceratonia siliqua L. Pods Extracts

Abstract: The present work was designed to investigate the effects of different extraction processes, namely ultrasonic-assisted, supercritical fluid, microwave-assisted and Soxhlet applied to carob pods. The total phenolic quantification and the antioxidant activity were assessed by the means of rapid in vitro spectrophotometric assays; the phenolic profile was identified using ultra-high performance liquid chromatography coupled to mass spectrometry. The results revealed that the phenolic compounds and the antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
2
3
0
2
Order By: Relevance
“…The results are similar to those obtained by Lopez-Fernandez et al 23 , who reported that methanol extract obtained by maceration gives the highest total tannin content (1.99±0.11mg CE/g dry weight). The results are similar to those of Mansouri et al 24 , who found that the methanol extract obtained by maceration gives the highest total tannins content (1.99±0.11 mg CE/g dry weight). In another study, Souhila and Mustapha, 25 reported that the Aqueous extract had the best tannin content of 4.09 mg CE/g dry weight.…”
Section: Resultssupporting
confidence: 91%
“…The results are similar to those obtained by Lopez-Fernandez et al 23 , who reported that methanol extract obtained by maceration gives the highest total tannin content (1.99±0.11mg CE/g dry weight). The results are similar to those of Mansouri et al 24 , who found that the methanol extract obtained by maceration gives the highest total tannins content (1.99±0.11 mg CE/g dry weight). In another study, Souhila and Mustapha, 25 reported that the Aqueous extract had the best tannin content of 4.09 mg CE/g dry weight.…”
Section: Resultssupporting
confidence: 91%
“…In the literature, there are many studies comparing different extraction methods to prepare an active extract. The solvent concentration, the extraction time, and the extraction temperature are the parameters that most influence the phytochemical profile of the extracts [ 15 , 35 , 36 ]. Generally, the ethanol–water mixtures have been found to be effective for the antioxidants’ extraction from botanical materials [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…They exert beneficial effects on dyslipidemia and interfere with glucose absorption mechanisms [ 12 , 13 , 14 ]. Many of these activities are related to the inhibiting potential of oxidant species [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Di sisi lain, pengamatan yang sama dilakukan untuk kandungan flavonoid total dari ekstrak carob yang terungkap sangat dipengaruhi oleh proses ekstraksi. MAE ternyata menjadi metode ekstraksi yang paling tepat untuk pemulihan carob flavonoid, menghasilkan nilai tertinggi (10,53 mg EK/g DM) (Mansouri et al, 2022). Di sisi lain, pengamatan yang sama dilakukan untuk kandungan flavonoid total dari ekstrak biji carob (Ceratonia siliqua L.) dari keluarga Fabaceae (kacang-kacangan), yang terungkap sangat dipengaruhi oleh proses ekstraksi.…”
Section: Skrining Fitokimiaunclassified
“…Di sisi lain, pengamatan yang sama dilakukan untuk kandungan flavonoid total dari ekstrak biji carob (Ceratonia siliqua L.) dari keluarga Fabaceae (kacang-kacangan), yang terungkap sangat dipengaruhi oleh proses ekstraksi. MAE ternyata menjadi metode ekstraksi yang paling tepat untuk pengukuran kadar flavonoid, menghasilkan nilai tertinggi (10,53 mg EK/g DM) (Mansouri et al, 2022).…”
Section: Skrining Fitokimiaunclassified